An MTT-based method for the in vivo quantification of myotoxic activity of snake venoms and its neutralization by antibodies - Lomonte, Bruno (1993)
The reduction of the tetrazolium compound MTT (3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyl-tetrazolium bromide) was used as the basis for the development of a simple method for the quantitative estimation of metabolically active skeletal muscle tissue remaining after in vivo venom-induced myonecrosis. Using the venom of the snake Micrurus nigrocinctus as a potent myotoxic agent, this MTT-based technique was evaluated in comparison with available methods based on the measurement of creatine kinase (CK) activity, and a quantitative histological technique considered as a reference. Homogenates of the gastrocnemius muscle prepared in the presence of 1% Triton X-100 reduced MTT and this activity correlated closely with the number of viable cells in the tissue, as determined by histological evaluation. After venom injection, residual MTT-reducing activity of muscle homogenates showed higher correlation to the myonecrosis index obtained by histological analysis, than residual muscle CK activity. Using the new MTT-based assay, the ability of an anti-M. nigrocinctus equine antivenom to neutralize venom myotoxins was studied. The myotoxic activity of the venom was completely neutralized using 4 ml antivenom/mg venom, with a 50% effective dose (ED50) value of about 2.5 ml/mg. The MTT-based method described should be useful in the estimation and standardization of anti-myotoxic potency of antivenoms, and in the screening of other neutralizing agents, as a convenient and reliable alternative to the time-consuming quantitative histological methods.